한국어판 폐경 특이형 삶의 질 측정도구의 신뢰도와 타당도 검증 - 박진희; 배선형; 정영미; Park, Jin-Hee; Bae, Sun Hyoung; Jung, Young-Mi (Journal of Korean Academy of Nursing, 2020)
Purpose: This study aimed to evaluate the validity and reliability of the Korean version of Menopause-Specific Quality of Life (MENQOL). Methods: The MENQOL was translated into Korean according to algorithm of linguistic validation process. A total of 308 menopausal women were recruited and assessed using the Korean version of MENQOL (MENQOL-K), the World Health Organization Quality of Life Brief Version (WHOQOL-BREF), and Center for Epidemiological Studies Depression Scale (CES-D-K). In estimating reliability, internal consistency reliability coefficients were calculated. Validity was evaluated through criterion validity and construct validity with confirmatory factor analyses using SPSS 23.0 and AMOS 25.0 software. Results: In item analyses, the "increased facial hair" symptom was excluded because of the low contribution of MENQOL-K. The confirmatory factor analysis supported good fit and reliable scores for MENQOL-K model, and the four-factor structure was validated (χ2=553.28, p<.001, NC=1.84, RMSEA=.05, AGIF=.85, AIC=765.28). The MENQOL-K consists of 28 items in 4 domains, including vasomotor (3 items), psychosocial (7 items), physical (15 items), and sexual subscales (3 items). There was an acceptable criterion validity with moderately significant correlation between MENQOL-K and WHOQOL-BREF. The Cronbach's α for the 4 subsacles ranged from .80 to .93. Conclusion: The MENQOL-K is a valid and reliable scale to measure condition-specific quality of life for perimenopausal and postmenopausal women. It can be used to assess the impact of menopausal symptoms on the quality of life of Korean women in clinical trials.